2010
DOI: 10.1186/1472-6882-10-16
|View full text |Cite
|
Sign up to set email alerts
|

A forced titration study of the antioxidant and immunomodulatory effects of Ambrotose AO supplement

Abstract: BackgroundOxidative stress plays a role in acute and chronic inflammatory disease and antioxidant supplementation has demonstrated beneficial effects in the treatment of these conditions. This study was designed to determine the optimal dose of an antioxidant supplement in healthy volunteers to inform a Phase 3 clinical trial.MethodsThe study was designed as a combined Phase 1 and 2 open label, forced titration dose response study in healthy volunteers (n = 21) to determine both acute safety and efficacy. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The changes noted in blood antioxidant capacity from pre to post intervention are similar to, albeit slightly less than, those reported in the previous two open-label designs using Ambrotose AO ® [15,16]. Moreover, our increases of approximately 22% in ORAC and 19% in TEAC are similar to other previously published work using either whole foods or antioxidant supplements.…”
Section: Discussionsupporting
confidence: 87%
“…The changes noted in blood antioxidant capacity from pre to post intervention are similar to, albeit slightly less than, those reported in the previous two open-label designs using Ambrotose AO ® [15,16]. Moreover, our increases of approximately 22% in ORAC and 19% in TEAC are similar to other previously published work using either whole foods or antioxidant supplements.…”
Section: Discussionsupporting
confidence: 87%
“…The potential studies identified in database searches were screened and ranked based on the plant active ingredient, to identify the plants with the highest number of published reports. The 10 most commonly studied PFS claimed to improve or enhance immune function identified in this study were: Andrographis paniculata (Green Chirayta) (Calabrese et al, 2000;See et al, 2002), Camellia sinensis (Tea) (Myers et al, 2010;Rowe et al, 2007), Corylus avellana (Common Hazel) (Savolainen et al, 2006;Savolainen et al, 2007), Garcinia mangostana (Purple Mangosteen) (Tang et al, 2009), Hibiscus sabdariffa (Roselle) (Beltran-Debon et al, 2010), Lycopersicon esculentum (Tomato) (Briviba et al, 2004;Markovits et al, 2009;Riso et al, 2006;Watzl et al, 1999;Wood et al, 2008), Olea europaea (Olive) (Alvarez-Cuesta et al, 2005), Pleurotus ostreatus (Oyster Mushroom) (Bergendiova et al, 2011;Bobovcak et al, 2010), Sambucus nigra (Elderberry) (Barak et al, 2002), and Vaccinium myrtillus (Bilberry) (Karlsen et al, 2010). The widespread consumption of several PFS obtained from these plants for enhancing immune function is well documented (Cassileth et al, 2009).…”
Section: Plant Food Supplements Investigated In Reviewmentioning
confidence: 99%
“…A total of 18 articles were eventually included in the final data extraction set. In order of prevalence 8 of these were based on double-blind randomised controlled trials (Alvarez-Cuesta et al, 2005;Bergendiova, Tibenska, & Majtan, 2011;Bobovcak, Kuniakova, Gabriz, & Majtan, 2010;Briviba et al, 2004;Rowe, Nantz, Bukowski, & Percival, 2007;Savolainen, Jacobsen, & Valovirta, 2006;Savolainen et al, 2007;Tang et al, 2009); 7 trials were conducted without placebo and/or randomisation assignment (Barak, Birkenfeld, Halperin, & Kalickman, 2002;Beltran-Debon et al, 2010;Calabrese et al, 2000;Markovits, Ben Amotz, & Levy, 2009;Myers et al, 2010;See, Mason, & Roshan, 2002;Watzl, Bub, Brandstetter, & Rechkemmer, 1999); and the remainder were based on studies of the following designs: a double-blind randomised controlled cross-over trial (Riso et al, 2006), a randomised controlled trial (Karlsen et al, 2010), and a randomised controlled cross-over trial (Wood, Garg, Powell, & Gibson, 2008). Though the study inclusion criteria was as broad as possible and criteria did not exclude specific trial designs, not all trial designs were encountered in the final 18 selected studies.…”
Section: Literature Search and Study Design Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that Tai Chi exercise can improve a number of medical conditions relevant to frail elders, including chronic heart failure, [69] hypertension, [1012] hyperlipidemia, [10, 13, 14] coronary artery disease, [15–18] chronic obstructive pulmonary disease, [1921] cardiorespiratory fitness, [2224] poor balance, [2528] reduced musculoskeletal strength and flexibility, [13, 22, 2931] Parkinson’s disease, [32] rheumatologic conditions, [3337] cognitive decline, [38, 39] and overall mood. [40] In a previous pilot study, we have shown that Tai Chi can be practiced successfully and without adverse effects by frail seniors living in supportive housing and results in significant improvements in balance, gait, and functional ability after only 12 weeks. [41] However, it remains to be determined whether a longer period of Tai Chi exercise can further improve the health of poor, frail seniors and reduce their health care utilization and costs.…”
Section: Introductionmentioning
confidence: 99%